Evolution and Tectonics of the Lithosphere in Northwestern Canada - Estève, Clément (Université d'Ottawa / University of Ottawa, 2020)
The lithosphere of northwestern Canada recorded more than 2.5 Gy of complex tectonic evolution, from the formation of the ancient cores of the continental lithosphere such as the Slave craton to the Phanerozoic Cordilleran orogeny with substantial variations in crust and upper mantle structures that led to the concentration of natural resources (i.e., diamonds in cratons). Present-day northwestern Canada juxtaposes a thin and hot Cordilleran lithosphere to the thick and cold cratonic lithosphere, which has important implications for regional geodynamics. Recently, seismic station coverage has drastically increased across northwestern Canada, allowing the development of seismic tomography models and other passive-source seismic methods at high resolution in order to investigate the tectonic evolution and dynamics of the lithosphere in this region. The P- and S-wave upper mantle structures of northwestern Canada reveal that the distribution of kimberlite fields in the Slave craton correlates with the margin of fast and slow seismic mantle anomalies, which could delineate weak zones in the lithosphere. Based on our tomographic models we identify two high-velocity seismic anomalies straddling the arcuate Cordillera Deformation Front that have controlled its regional deformation, including a newly identified Mackenzie craton characterized by high seismic velocities extending from the lower crust to the upper mantle to the north of the Mackenzie Mountains. Furthermore, our P-wave tomography model shows sharp velocity contrasts beneath the surface trace of the Tintina Fault. Estimates of seismic anisotropy show a progressive rotation of fast-axis directions when approaching the fault zone. Together, they provide seismic evidence for the trans-lithospheric nature of the Tintina Fault. We further propose that the Tintina Fault has chiseled off small pieces of the Laurentian craton between the Late Cretaceous and the Eocene, which would imply that large lithospheric-scale shear zones are able to cut through small pieces of refractory cratonic mantle and transport them over several hundred kilometers.
Keywords: Seismic Tomography; Seismic Anisotropy; Northern Canadian Cordillera; Tectonophysics